The influence of organizational culture, downward accountability, and knowledge sharing on Malaysian nonprofit organizations effectiveness: From employees perspective / Nurul Hidayana Mohd Noor - Nurul Hidayana , Mohd Noor (2017)
This study was conducted to examine the influence of organizational culture, downward accountability, and knowledge sharing on the effectiveness of Malaysian nonprofit organizations (NPOs). This study also aimed to examine the mediation effect of knowledge sharing in the relationships between organizational culture, downward accountability, and NPOs effectiveness. Employing a mixed method design, a survey study of 369 employees was first conducted and data were interpreted based on structural equation modeling (SEM). Then, six key informants were interviewed and data were analyzed using deductive and inductive approach. Two key findings emerged from the analyses. First, organizational culture, downward accountability, and knowledge sharing were significantly positive influenced NPOs effectiveness. Second, knowledge sharing fully mediated the relationship between organizational culture and NPOs effectiveness, whereas it partially mediated the relationship between downward accountability and NPOs effectiveness. Overall, the findings advanced prior research by providing new insights on the overview of defined organizational factors that can potentially determine NPOs effectiveness. Upon theoretical implications, this study also offered several policies and practical implications. Malaysian government needs to improve NPOs capacity through support and training, to ensure sufficient resources to NPOs, to promote collaboration between NPOs, private entities, and public sector, to establish a national code of conduct, and to strengthen the existing regulatory framework for Malaysian NPOs. Meanwhile, NPOs itself need to integrate their organizational strategy with system elements, and this can be done by conducting organizational assessment, by adapting and employing best practices, and by supporting and maintaining the uniqueness of organizational factors. Then, NPOs also need to focus on organizational practices that positively impact knowledge sharing environment. Since NPOs work nature is merely based on volunteerism, NPOs need to motivate their employees to share knowledge. In this case, intrinsic motivation could help to boost up employee motivation and commitment to share knowledge. Finally, derived as a new theme from the qualitative data, NPOs also need to focus on important leadership aspects such as the improvement of existing leadership and the development of new leadership. In the final section of this thesis, limitations of this study and suggestions for future research were discussed.